2016
DOI: 10.1021/acs.analchem.6b00519
|View full text |Cite
|
Sign up to set email alerts
|

De Novo Sequencing of Complex Mixtures of Heparan Sulfate Oligosaccharides

Abstract: Here, we describe the first sequencing method of a complex mixture of heparan sulfate tetrasaccharides by LC-MS/MS. Heparin and heparan sulfate (HS) are linear polysaccharides that are modified in a complex manner by N- and O-sulfation, N-acetylation, and epimerization of the uronic acid. Heparin and HS are involved in various essential cellular communication processes. The structural analysis of these glycosaminoglycans is challenging due to the lability of their sulfate groups, the high heterogeneity of modi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
36
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 53 publications
2
36
0
Order By: Relevance
“…In this respect, previous studies have shown that a Z 2 /Y 2 ratio of ~0.3 of tetrasaccharides is indicative of IdoA, while a Z 2 /Y 2 ratio of ~0.9 is indicative of GlcA. 20b …”
Section: Resultsmentioning
confidence: 89%
See 3 more Smart Citations
“…In this respect, previous studies have shown that a Z 2 /Y 2 ratio of ~0.3 of tetrasaccharides is indicative of IdoA, while a Z 2 /Y 2 ratio of ~0.9 is indicative of GlcA. 20b …”
Section: Resultsmentioning
confidence: 89%
“…Therefore, the Robo1-binding octasaccharides were further analyzed by sequential permethylation, desulfation, and pertrideuteroacetylation followed by online separation and structural analysis by MS/MS. 20 By replacing the polar and labile sulfates with much more stable and hydrophobic trideuteroacetyl groups, oligosaccharides were obtained that could be separated by reverse-phase capillary HPLC and fragmented by MS/MS without loss of information on sites of modification. The structural complexity of HS oligosaccharides increases exponentially as oligosaccharides become larger, and therefore manual interpretation of MS/MS spectra and identification of isomeric sequences is challenging.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…What often remains to be determined is biochemical analysis of the HS structures that are made in the absence of one enzyme. This has been hampered in the past by the requirement of large amounts of HS to be analyzed, recently more sensitive techniques such as LC-MS/MS have been used to sequence complex mixtures of HS tetrasacharides (65). …”
Section: Introductionmentioning
confidence: 99%